2011
DOI: 10.1186/1757-7241-19-73
|View full text |Cite
|
Sign up to set email alerts
|

Association between a single-pass whole-body computed tomography policy and survival after blunt major trauma: a retrospective cohort study

Abstract: IntroductionSingle-pass, whole-body computed tomography (pan-scan) remains a controversial intervention in the early assessment of patients with major trauma. We hypothesized that a liberal pan-scan policy is mainly an indicator of enhanced process quality of emergency care that may lead to improved survival regardless of the actual use of the method.MethodsThis retrospective cohort study included consecutive patients with blunt trauma referred to a trauma center prior to (2000 to 2002) and after (2002 to 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 37 publications
1
106
0
9
Order By: Relevance
“…19 In addition, the duration of hospital stay is reportedly shorter in MSCT protocols. 19,20 Hutter et al reported a mortality rate of 23.3% in MSCT protocol and 9.7% in conventional CT protocol. 20 In a study by Gupta et al 1812 of 2804 imaging procedures were considered necessary by both emergency physicians and trauma surgeons and a critical pathology was detected in 123 (7%) imaging procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In addition, the duration of hospital stay is reportedly shorter in MSCT protocols. 19,20 Hutter et al reported a mortality rate of 23.3% in MSCT protocol and 9.7% in conventional CT protocol. 20 In a study by Gupta et al 1812 of 2804 imaging procedures were considered necessary by both emergency physicians and trauma surgeons and a critical pathology was detected in 123 (7%) imaging procedures.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Hutter et al reported a mortality rate of 23.3% in MSCT protocol and 9.7% in conventional CT protocol. 20 In a study by Gupta et al 1812 of 2804 imaging procedures were considered necessary by both emergency physicians and trauma surgeons and a critical pathology was detected in 123 (7%) imaging procedures. They concluded that CT had an important role for treatment planning, mortality, and morbidity in multitrauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lower doses of radiation should be considered, especially in children and the young. Although there are no Brazilian data on the subject, it is estimated that, in the United States, between 1.5 and 2% of all diagnosed neoplasms are related to hospital radiation use 5 . Such data is relevant to this discussion, since full-body CT scans generate a radiation dose of 10-30mSv 6,8,[11][12][13][14][15] , which is up to 1,000 times greater than that of a PA chest X-ray, whose estimated dose is 0.01mSv 16 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…There are other issues in literature that reinforce the safety of the conduct of cases through conventional studies, leaving the CT as an supplementary examination. Firstly, the effectiveness of the reduction in mortality by way ofa full-body CT scan during initial evaluation remains uncertain in literature [4][5][6][7][8][9] . There is a lack of important randomized and controlled studies on the subject and there are articles that do not show an associated reduction in mortality 4 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…(Harris et al, 2008Holly et al, 2001Martins et al, 2003;Cristante e Jorge, 2012;Lutaka et al, 2012 ;Marcon et al, 2012;Miller et al, 2010;Schmidt et al, 2009;Rosi, 2011 (Kattail et al, 2009;Hunter et al, 2011;Maurer et al, 2009;Mulligan et al, 2010;Schmidt et al, 2009;Sampson et al, 2006;Sun et al, 2010).…”
Section: 9%mentioning
confidence: 99%